Program Praktik Pengalaman Lapangan dan Hubungannya dengan Kompetensi Mahasiswa Prodi Manajemen Pendidikan Islam FTIK UIN Alauddin Makassar - Ali Nahruddin Tanal; Muhammad Yahya; Kamsinah Kamsinah (Institut Agama Islam Negeri (IAIN) Palopo, 2019)
This study aims to determine the internship program called PPL implemented by student of Islamic Educational Management Program at UIN Alauddin Makassar, and the relationship between the internship program and the competencies of students involved. This research is classified as field research using quantitative methods. Data were collected using a questionnaire, and analyzed using quantitative descriptive analysis techniques. The product-moment formula is used to test the relationship between the two variables. The results of the data analysis show that the relationship between the intership program and student competency is in a low category, or there is no relationship between the two. Therefore, it was concluded that the field experience program was not relevant to be applied for student of Islamic Educational Management Program who were not in accordance with the competencies of the students.